Abatement of Cd in rice grain and toxic risks to human health by the split application of silicon at transplanting and jointing period. (15th January 2022) - Pan, Bogui; Cai, Yixia; Liu, Bingquan; Cai, Kunzheng; Lv, Wenwen; Tian, Jihui; Wang, Wei
Abstract: Silicon (Si) has the potential to ameliorate the toxic effects of cadmium (Cd) on rice growth and mitigate Cd-uptake by rice under Cd-contaminated soil. However, it is not completely clear whether there are differences in the impacts of different Si management on the chemical behavior of Cd in soil-rice system under Cd-contaminated paddy field. Here, pot trials were conducted to explore the effects of three modes of Si application (T-applying Si at transplanting stage, J-applying Si at jointing stage, TJ-applying Si at transplanting stage and jointing stage with a ratio of 50% to 50%) on the accumulation of Cd in rice grain and the toxic risk of Cd on human health in rice consumption under Cd-polluted soil (4.21 mg·kg −1 ), and that without Si application was used as control (CK). Results showed that rice growth and Cd-retention in root were enhanced by Si application, and the retention of Cd in TJ root was the highest, reaching 82.36%∼84.06% of total Cd absorbed by rice plant. TJ also elevated soil pH and CEC value significantly during the whole growth period, diminished Cd availability and converted exchangeable-Cd into residual-Cd in soil. Moreover, Si application reduced Cd concentration in iron plaque, while TJ had the lowest concentration of DCB-Cd and the highest molar ratios of Fe/Cd and Mn/Cd. The bioaccessibility of Cd from grains and cooked rice were decreased by Si application. Compared with T and J, the hazard quotient of digestion from cooked white rice of TJ in gastric phase was reduced by 19.61% and 21.94%, respectively. In brief, TJ had more efficiency on reducing the Cd availability in soil during the rice growing period, promoting the retention of Cd in root, decreasing Cd uptake by rice plant and distribution to grains, as well as the bioaccessibility of Cd from cooked rice. These results also provide a novel strategy of Si application to decrease the risk of Cd migration in the soil-rice-humans system and simultaneously promote rice yields. Graphical abstract: Image 1 Highlights: The ratio of Cd retained in root treat by TJ was the highest among all treatments. TJ facilitated the decline of the Cd bioavailability by converting more exchangeable-Cd into residual-Cd in soil. The iron plaque of TJ with higher molar ratios of Fe/Cd and Mn/Cd obstructed Cd absorption. The Cd bioaccessibility and toxic risk to human health from cooked rice treated by TJ were decreased obviously.